Sustainability in an Organization : Motivations´ Perceptions, Limitations, and Paradoxes - Svobodová, Markéta; Malý, Milan, 1936-; Chytková, Zuzana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
Sustainable development has recently become one of the basic directions of strategical management of modern organizations. It creates the prerequisites for increasing the competitive capacity of the company in the future, to secure the organization’s sustainability (existence), and it is therefore in the interest of all interested parties - stakeholders, to create the best possible conditions for the implementation of sustainability in the company. However, the implementation of sustainability is still challenging for organizations, due to insufficient motivations toward sustainability, existing barriers to sustainability as well as related paradoxes which have not been accepted/ resolved by the organizations’ management. Thus, the preconditions for the implementation of sustainability are the motivation of all parties toward this realization, mitigating or eliminating limitations to sustainability, and working with/ accepting paradoxes. Nevertheless, the study of literature shows that there are still issues in this area of sustainability implementation at organizations, that have not been completely clarified yet - literature gaps that would be useful to fill in by a detailed empirical study to understand these three interconnected phenomena hindering successful implementation of sustainability in organizations, more and thus help to overcome them. Thus, the main, overarching, aim of the dissertation is to understand how the implementation of sustainability at the selected large organization is hindered, specifically by exploring motivations toward sustainability across the organizational hierarchy, existing limitations to sustainability, and related sustainability paradoxes. In connection with that, the aim is also to explore and understand more the relationships/ interactions of these three phenomena influencing sustainability implementation in an organization.
For data collection, a single case study including in-depth semi-structured interviews, participative observation, and archival documents is employed. For data analysis, coding and thematic analysis are used.
Vedoucí práce: Milan Malý
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations